The threat of reputation risk in social media - Heikonen, Maija (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Nowadays, because of the huge success of social media, the vulnerability of corporate reputation is a more critical concern, and active monitoring of reputation risk is becoming increasingly important in social media. A favorable reputation is crucial in retailing, because it increases, e.g., the loyalty among the customers and their intentions to purchase. From the academic point of view, there is a need for more research concerning reputation risk, particularly in the context of social media. Social media monitoring has gradually become common and more important in companies, but the lack of appropriate monitoring has been noticed to be a weakness in many companies. The general purpose of this study is to describe how retail companies try to identify and control reputation risk by monitoring threatening conversations in social media. The purpose was addressed by answering the following three research questions: 1. How do retailers perceive corporate reputation and reputation risk? 2. How significant are social media, social media strategy, and social media monitoring in the identification and control of corporate reputation risk? 3. What kinds of challenges have retailers faced in social media monitoring, and how would they develop the practices and tools of monitoring? The concepts of corporate reputation, reputation risk, social media, and social media monitoring from the point of view of reputation management are discussed in the theoretical framework. The study adopts the managerial perspective. In order to attain the research purpose, an empirical qualitative study was conducted. The data were gathered by means of semi-structured interviews from retail companies in Finland. Altogether, eight interviews were carried out. This study gives more support to the proactive approach to the management of reputation risks. The findings of this study indicate that the threat of reputation risk is a more significant concern today in retailing because of social media. Reputation management in social media can be tricky, but with the help of efficient and appropriate tools and practices, companies may be able to manage it. The possibility to identify threatening conversations at an early stage was considered as the main advantage of social media monitoring. If negative information is presented in social media, companies should always take it into account fast and adapt the actions of communications accordingly. The findings support the idea that more effective tools and practices related to social media monitoring are needed.